2012
DOI: 10.3892/or.2012.1747
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of aquaporins in human biliary tract carcinoma

Abstract: Abstract. Aquaporins (AQPs) are important in controlling bile formation, however, the exact role of AQPs in human biliary tract carcinogenesis has not been clearly defined. In this study, we analyzed AQP-1, -4, -5 and -8 expression immunohistochemically using tissue microarrays (TMAs) in 81 samples. (45 gallbladder carcinomas and 36 bile duct carcinomas). The survival of patients with high AQP-5 expression was longer compared to that of patients with low AQP-5 expression (P=0.017). Cox's proportional hazard mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
(40 reference statements)
2
19
0
Order By: Relevance
“…In order to avoid epithelial cell contamination during venipuncture, all samples were collected after discarding the first 2 ml blood. Red blood cells (RBCs) were mixed with 45 ml lysis buffer (155 mM NH 4 Cl, 10 mM KHCO 3 , 0.1 mM EDTA), followed by rotation for 8 min and centrifugation (600 x g for 5 min) to remove RBCs. Resulting cell pellet was resuspended in PBS and subsequently incubated with 0.5 ml of antileukocyte surface marker CD45 monoclonal antibody coated magnetic beads for 30 min, followed by separation of magnetic beads using a magnetic stand (Promega, Madison, WI, USA).…”
Section: Isolation Of Normal Colon Cells and Culture Of Colorectal Camentioning
confidence: 99%
See 1 more Smart Citation
“…In order to avoid epithelial cell contamination during venipuncture, all samples were collected after discarding the first 2 ml blood. Red blood cells (RBCs) were mixed with 45 ml lysis buffer (155 mM NH 4 Cl, 10 mM KHCO 3 , 0.1 mM EDTA), followed by rotation for 8 min and centrifugation (600 x g for 5 min) to remove RBCs. Resulting cell pellet was resuspended in PBS and subsequently incubated with 0.5 ml of antileukocyte surface marker CD45 monoclonal antibody coated magnetic beads for 30 min, followed by separation of magnetic beads using a magnetic stand (Promega, Madison, WI, USA).…”
Section: Isolation Of Normal Colon Cells and Culture Of Colorectal Camentioning
confidence: 99%
“…Water molecules play a significant role in the progression of malignant epithelial tumors, an understanding of which is thus important in anticancer treatment strategy (4). Aquaporins (AQPs) are a family of membrane water channels that are required for the transport of water through many secretory and absorptive epithelia.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that KLF4 . On the basis of the total score (the sum of the intensity and distribution scores), each patient was classified into one of two groups: The low expression group (total score, 0-2) or the high expression group (total score, 3-5) (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that AQP-5 may be involved in the differentiation of human gastric carcinoma cells [6]. We also analyzed AQP-1, -4, -5, and -8 expression immunohistochemically using tissue microarray (TMA) in 81 biliary tract carcinoma samples [15]. Our results suggested that AQP-5 expression may be associated with prognosis and drug sensitivity in biliary tract carcinoma, although gallbladder and bile duct slightly differ in generation and organ function.…”
Section: Introductionmentioning
confidence: 99%